The Utilization of Games in Learning Calculation Ability (Accounting) Based on Android - Meiryani; Udjaja, Yogi; Jeviro, Jevon; Sabrina, Sasya (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to find out what kind of game which is interesting and could help kids’ motoric skills growth. The advantage of this research is to produce a game that could become mathematics learning media for 4 to 6 years old kids. The method that used to make this research is Game Development Life Cycle (GDLC), where the research includes the idea of game concept, asset making, programming, testing, and evaluation. The conclusion of this research is able to produce a game titled “Asyiknya Bermain Sambil Berhitung”, this game’s genre is endless run that has a mathematics element of adding-substracting from 1 to 20 in it. The result of this research is from 10 maths question had been given, 19 from 45 kids are able to answer 9 to 10 questions correctly.